Spicy business of Saudagar Rasa and its heritage gourmet - Mohd Sharif, Siti Nurhayati Khairatun (I I U M Press, 2021)
This case study presents a food manufacturer, Noraz Berkat Trading (NBT), one of the food manufacturing SMEs in Malaysia which is involved in producing spice-based premixes and seasonings of authentic Malaysian heritage cuisines. A development life cycle and SWOT analysis are the focal points illustrating the survival of NBT in the food manufacturing industry. Primary data were obtained from a series of interview sessions with the founder of the company and secondary data was generated from social media platforms and websites. Upon completion of learning the case study, the students should be able to identify the phases of the development life cycle in SME business and to explain the strengths, weaknesses, opportunities, and threats encountered by the SME.